2014
DOI: 10.4236/ojra.2014.42012
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Measurements of Knee Joints in Indian Population: Comparison to Current Knee Prostheses

Abstract: Most of the existing total knee arthroplasty (TKA) implants are designed to suit the knee anatomy of the Western population. Studies have shown that there are striking variations in knee morphology between the Asian and Western population. We conducted a case-control study to investigate the anthropometry of the Indian arthritic knees using three dimensional knee models and evaluated them morphologically against commercially available TKA implants. Measurements included the mediolateral width (ML), anteroposte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 15 publications
2
10
0
Order By: Relevance
“…Thus our results suggest that Western implants may not be suitable for Indian patients. The limitation of this study was that we measured the unresected sizes of 3D reconstructed knee, but our results were similar to other Indian study [10] . Also it was short term single institutional study, with smaller sample size.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Thus our results suggest that Western implants may not be suitable for Indian patients. The limitation of this study was that we measured the unresected sizes of 3D reconstructed knee, but our results were similar to other Indian study [10] . Also it was short term single institutional study, with smaller sample size.…”
Section: Discussionsupporting
confidence: 74%
“…Data of Indian knee morphometry of healthy and non osteoarthritic knee was lacking [10] . We studied the knee morphometry of Indian healthy and non osteoarthritic knee.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current TKA implants available are designed based on morphometric measurements obtained from a Western/Caucasian population. As many other studies but few in India 1 2 show the risk of component oversizing is more common in Asians, as they are of smaller built and stature. 3 4 5 This study looks into the intraoperative measurements of distal femoral dimensions of patients undergoing TKA in our institute, the ML mismatch, gender variations, correlation of ML mismatch with gender, and the type of implant used.…”
Section: Introductionmentioning
confidence: 79%
“…Most of the existing TKA implants are designed to suit the knee anatomy of the Western population. Studies have shown that there are striking variations in knee morphology between Western and Asian populations [ 13 ]. The implants for arthroplasty and surgical fixation in fractured patella can be customized according to the morphometry.…”
Section: Discussionmentioning
confidence: 99%